The Management for Over Nutrition of Village Health Volunteer in Chaiyaphum Province - Meknanthaphaisit, Ammara; Singhalert, Rungson; Sayruksas, Daenvichai (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: The Ministry of Public Health is aware of the health problems that occur when people are obese and therefore has a campaign for the project “Thai people without belly” or “Lose weight and reduce disease”. To see the health problems that will follow in the future, people who are at risk for abdominal obesity are those who consume more than the body needs, consuming starches, high sugar, and high fat. This research aimed 1) to analyze causal factors affecting over nutrition of village health volunteers in Chaiyaphum Province, 2) to design a model of management for over nutrition of village health volunteers, and 3) to implement and evaluate the model of management for over-nutrition of village health volunteer. Methodology: The research methodology was divided into 3 phases. 1) analysis of causal factors, 2) design of a model, and 3) implementation and evaluation of a new model. Phase 1 focused on analyzing causal factors that affect over nutrition of village health volunteers in Chaiyaphum Province, and analyzing the relationships between the causal factors to the empirical data. The target population of consisted 392 village health volunteers of overnutrition in Chaiyaphum Province from normal group 196 and abnormal group 196. The data were collected by questionnaires. Discriminant analysis was used to analyze. The causal factors affecting the dependent variables were analyzed with the empirical data. Phase 2 focused on designing a model of management for the over-nutrition of village health volunteer for over-nutrition village health volunteers based on the data from phase 1. The model was designed through a workshop of twenty-five participants. The focus group method was employed for discussion on the model of management for overnutrition of village health volunteers, and the developed model was assessed by three experts. Phase 3 focused on implementing and evaluating the model. The model was implemented on 30 experimental participants, and the model evaluation was identified by the comparison of the research results before and after model implementation, and the comparison of the results of the experimental groups and control group. Multivariate Analysis of Covariance was employed for data analysis. The Covariance was a score of waist circumference. Results: The findings were as follows: (1) According to the analysis of the relationship and the empirical data, the finding showed that 4 factors significantly affected the over-nutrition of village health volunteers in Chaiyaphum Province at the .05 level. The factors were awareness (0.779), activity and exercise behaviors (-0.168), eating behaviors (0.155), and motive (0.079). (2) The model of management over the nutrition of village health consisted of 8 activities: 1) fat, 2) power, 3) good body, 4) eat for life, 5) best food, 6) fit and firm target, 7) buddy, and 8) exercise. (3) The management for the overnutrition of village health volunteers after implementing the model was better than before implementing the model. The experimental groups and control groups were different at the .05 level of statistical significance. Conclusion: Factors influencing the prevalence of overnutrition among community health volunteers in Chaiyaphum province had statistically significant relationships, with awareness, physical activity behavior, dietary behavior, and motivation being the most significant. The developed overnutrition management guidelines consist of 8 activities, and the experimental results indicate their effectiveness compared to the control group, showing statistically significant differences.